Trial of Labour or Elective Repeat Caesarean Section in Women who have had one previous caesarean section: An assessment of women's attitudes, knowledge and preferences - Ahmed, Tasneem (Department of Obstetrics and Gynaecology, 2020)
INTRODUCTION Caesarean section (CS) is one of the most frequently performed major abdominal surgeries in the world. There has been a global increasing trend in CS rates over the past three decades, particularly in women who have had one previous CS. Vaginal birth after caesarean section (VBAC) is a safe option and is still strongly recommended by all international authorities with success rates ranging from 60% to 80%. However, women's preference for VBAC vs elective repeat caesarean section (ERCS) remains very poorly understood in South Africa (SA) as very few studies have addressed women's preference for mode of delivery. Repeat caesarean delivery (CD) is reported as the single largest contributor to the escalating CS rate worldwide. So why do women choose repeat CD? Evidence suggests that fear, health care worker influence, social stigma, cultural practise and religious beliefs can significantly influence the attitude toward CS. South African data remains limited and we are yet to ascertain how women make their choice and what drives their specific preferences. The rationale behind this study therefore was to gain better insight into why the women in Cape Town choose VBAC or ERCS and to ascertain to what extent their knowledge, attitude and preferences influence their choice. In so doing, we were able to highlight key findings in order to attempt to reduce the increasing CS rate in our country. AIMS AND OBJECTIVES The primary objective was to explore women's knowledge, attitudes and preferences for VBAC or ERCS after one previous CS, from 36 weeks gestation, attending antenatal care at Mowbray Maternity Hospital (MMH) and New Somerset Hospital (NSH). The secondary outcome was to describe the major reasons for their preferred mode of delivery. METHODOLOGY A prospective descriptive study was conducted over four months, of pregnant participants with one previous lower uterine segment caesarean section (LUSCS), attending antenatal care at MMH and NSH. Participants were recruited from 36-41weeks gestation. Participants over the age of 18 years with one previous LUSCS were eligible for inclusion. Participants with a medical indication for CS were excluded. An interview-based questionnaire, previously 11 adapted for use in a Cape Town antenatal population regarding women's knowledge, attitudes and preferences for mode of delivery was conducted at a routine antenatal visit. In addition, basic obstetric and socio-demographic data was abstracted from their folders. A descriptive analysis of participants' preferences for mode of delivery was completed, with subgroup comparisons. The Fisher's Exact test was used in all the statistical analyses that involved categorical variables whilst continuous variables were analysed using t-tests. RESULTS The study included 100 participants who were eligible for VBAC. Of the participants, 51% preferred ERCS whilst 49% preferred VBAC. Married couples and those in co-habiting relationships, more frequently chose VBAC compared to single participants, who more frequently chose ERCS. Participants were greatly influenced by the opinion of the HCW, particularly if ERCS was suggested, they were likely to choose a CS (p=0.001). If a previous history of long or obstructed labour was reported, participants were inclined to choose ERCS. Fear was identified as a major determinant as 78.4% cited fear of vaginal birth as their reason for preferring a CS. History of previous CS (88.2%) and fear of the risks associated with VBAC were the main reasons cited for their preference. In the group who preferred VBAC, 89.8% were of the perception that VBAC would allow them to recover faster and 87.7% desired to be home sooner therefore, favouring their choice. Whether or not the participants had a previous vaginal delivery or VBAC, it did not affect their preference for mode of delivery in a statistically significant manner. CONCLUSION This study which explored knowledge, attitudes and preferences of women who had had one previous CS, concerning their preference for mode of delivery, is one of the first to be done in South Africa. Despite all participants being medically eligible for VBAC, only 49% preferred this option, the remaining 51% preferring ERCS. Significant determinants of their choice were unstable relationships, influence of the doctor, concern about uterine rupture and fear of labour and unpredictability. Knowledge of the complications of ERCS and VBAC was very limited. This information is useful to design further research to improve understanding of these issues and to design services in a way to overcome the identified problems. In particular, women must be provided non-biased evidence-based information in order to foster a relationship of trust with the health care worker, in assisting her to make an informed decision. Similarly improving respectful competent care of women in labour with better attention to alleviating labour pain, will assist in reducing fear.